THE EFFECT OF MICROSTART ENZYMES ADDITION AND AERATION TIME ON COD REDUCTION - Z. Wathoni, Akda; Sayuti, Muhamad; Nugraha, Ucu (International Journal of Psychosocial Rehabilitation, 2020)
In a wastewater treatment plant in one of the companies in Karawang, some enzyme was added in the aeration tank which aims to reduce the COD content in wastewater. In this study, an observation will be conducted on how much influence the addition of enzyme doses on COD decrease of wastewater. The research method uses the Design of Experiments (DOE) method. Variables include COD content as an dependent variable and enzyme doses as an independent variable with variations in concentration: 0 ppm, 50 ppm, 100 ppm and 150 ppm and variations in aeration time: 0-, 1-, 2- and 3-hour, data collected directly based on the results of sampling which will be analyzed for COD content. Based on the results of research on enzyme doses significantly influence the decrease in COD content base on the value of f-count > f-table Anova factorial RAL = 43 177.30 > 2.82. In addition, the aeration time also has a significant effect on reducing the COD content. This can be seen from the value of f-count > f-table Anova factorial RAL = 838.63> 2.82. Enzyme dosage and contact time has a significant effect on decreasing COD content. Multiple Linear Regression is Y = 101.303 - 0.055X1 - 19.444 X2 + e. The correlation coefficient number is 95.7% and the coefficient of determination value is 91.6%. From the research data it can be seen that the dose of the micro start enzyme and the optimum contact time is 100 ppm with a contact time of 2 hours. This is indicated by the declining value of COD content reaching 56.3%.